Escaping the labyrinth : the Cretan neolithic in context (Sheffield studies in Aegean archaeology, 2010)
Introduction /Valasia Isaakidou andPeter D. Tomkins --Approaching the labyrinth /John D. Evans --Time, space and the reinvention of the Cretan Neolithic /Peter D. Tomkins --A sea of agency: Crete in the context of the earliest Neolithic in Greece /Kostas Kotsakis --The knapped stone technology of the first occupants at Knossos /James Conolly --"The fauna and economy of Neolithic Knossos" revisited /Valasia Isaakidou --Figurin' out Cretan Neolithic society: anthropomorphic figurines, symbolism and gender dialectics /Maria Mina --Living with the dead: a re-consideration of mortuary practices in the Greek Neolithic /Sevi Triantaphyllou --Stones of contention: regional axe production and hidden landscapes in Neolithic Crete /Thomas F. Strasser --Neolithic Katsambas revisited: the evidence from the house /Nena Galanidou andKatya Manteli --The Neolithic settlement of Phaistos revisited: evidence form ceremonial activity on the eve of the Bronze Age /Simona Todaro andSerena Di Tonto --Obsidian in transition: the technical reorganization of the obsidian industry from Petras Kephala (Siteia) between Final Neolithic IV and Early Minoan I /Cesare D'Annibale --The Final Neolithic (Late Chalcolithic) to Early Bronze Age transition in Crete and the South-East Aegean Islands: changes in settlement patterns and pottery /Krzysztof Nowicki --Between a rock and a hard place: coping with marginal colonisation in the Later Neolithic and Early Bronze Age of Crete and the Aegean /Paul Halstead --The Neolithic-Early Bronze Age transition in Crete: new evidence from the settlement at Petras Kephala, Siteia /Yiannis Papadatos --Long after hippos, well before palaces: a commentary on the cultures and contents of Neolithic Crete /Cyprian Broodbank --The Neolithic of Crete, as seen from outside /Andrew Sherratt andSusan Sherratt.